2018
DOI: 10.5336/ophthal.2016-51693
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus in a Case with Scleroderma: A Rare Coexistence

Abstract: cleroderma or systemic sclerosis (SSc) is a chronic multi-system disorder predominantly affecting the skin, musculoskeletal, gastrointestinal, pulmonary and renal systems. 1 Corneal involvement in SSc is rare. Filamentous keratitis, exposure keratitis (secondary to lid changes), peripheral ulcerative keratitis, pellucid marginal degeneration and increase in the central corneal thickness (CCT) have all been reported to be associated with SSc. 2-5 Keratoconus is a progressive non-inflammatory corneal ectasia. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…27 Corneal ectatic disorders, such as keratoconus, have also been associated with SSc; although they are defined as noninflammatory progressive diseases of the cornea, strong associations between keratoconus and various immune-related disorders have been described. 28 Keratoconus was first found to occur in SSc patients in a recent case report by Anayol et al 29 Because the incidence of keratoconus is relatively low in the normal population, in which it occurs in an estimated 13.3 cases per 100,000, 30 the importance of corneal alterations in SSc seems to be further emphasized by our study, in which one patient manifested keratoconus, and other cases showed with corneal scar formation, e.g., dellen, and severe keratitis. Other infrequent corneal lesions, such as filamentous keratitis, 5 bilateral peripheral ulcerative keratitis, 31 pellucid marginal degeneration 32 or keratomalacia 33 , have also been described.…”
Section: Corneamentioning
confidence: 99%
“…27 Corneal ectatic disorders, such as keratoconus, have also been associated with SSc; although they are defined as noninflammatory progressive diseases of the cornea, strong associations between keratoconus and various immune-related disorders have been described. 28 Keratoconus was first found to occur in SSc patients in a recent case report by Anayol et al 29 Because the incidence of keratoconus is relatively low in the normal population, in which it occurs in an estimated 13.3 cases per 100,000, 30 the importance of corneal alterations in SSc seems to be further emphasized by our study, in which one patient manifested keratoconus, and other cases showed with corneal scar formation, e.g., dellen, and severe keratitis. Other infrequent corneal lesions, such as filamentous keratitis, 5 bilateral peripheral ulcerative keratitis, 31 pellucid marginal degeneration 32 or keratomalacia 33 , have also been described.…”
Section: Corneamentioning
confidence: 99%
“…The first case report of the association of SSc with ectasia of the cornea has been documented by Anayol et al in 2018 in a 50-year-old female with keratoconus. 6 The steep K values in their patient were 49.47/ 53.59 D and pachymetry values were (455/423) microns. Considering age of the patient, the chances of any progression occurring in her were unlikely, therefore, surgical intervention was not deemed to be necessary and their patient was advised spectacle prescription.…”
Section: Discussionmentioning
confidence: 85%
“…Peripheral corneal thinning associated with scleroderma is more often inflammatory and ulcerative. 6 Also considering the fact that SSc causes fibrosis involving multiple organs, there are increased chances of corneal scarring in the healing process post CXL. Bearing this in mind, undertaking CXL in patients of SSc may prove to be risky.…”
Section: Discussionmentioning
confidence: 99%
“…In einer kleinen Studie von Grennan et al traten bei diesen Patienten zwar nicht häufig trockene Augen und retinale Anomalien auf, aber 50% der Patienten wiesen Anomalien der Aderhaut auf, bei denen es sich um Bereiche ohne Perfusion handelte [130]. Ein Patient mit Keratokonus wies eine verringerte Hornhautdicke, eine schwere Keratokonjunktivitis sicca und eine verringerte Tränenstabilität zusätzlich zur Hornhautverkrümmung auf [131]. Iris-Transillumination tritt auf, wenn die Sklerodermie die Pigmente der Iris beeinträchtigt [132].…”
Section: Autoimmunerkrankungen Und Ihre Auswirkungen Auf Das Augeunclassified